PENGEMBANGAN INSTRUMEN PENILAIAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA PADA MATERI ASAM BASA - Amalia, Nunung Fika; Susilaningsih, Endang (Jurnal Inovasi Pendidikan Kimia, 2014)
In order to achieve the national education goals, students are required to have critical thinking skills, especially on abstract lesson such as chemistry. Preliminary research conducted at one of high school in Ambarawa found that the assessment instruments used have not been oriented toward critical thinking skills. The purpose of this study is to investigate the process of developing critical thinking skills assessment instruments, to obtain the innovation critical thinking skills assessment instruments that can measure students critical thinking skills, and acquire critical thinking skills assessment instruments that meet criteria for valid and reliable. The research is a Research and Development. The procedures are the preliminary stages of research and development stages. Preliminary stages are divided into two, namely the field studies and literature studies. The development stages are divided into several parts, namely 1) develop the type of instrument, 2) validation by expert, 3) a limited scale trial, 4) large-scale trials and 5) implementation of the product. The results of this study indicate that the type of instrument used in schools have cognitive taxonomic level C1 to C2 and sometimes C3. Assessment instruments developed was essay test analysis, student activity sheets, and testoriented problem solving students critical thinking skills. Assessment instruments that have been developed in this study is valid and reliable and positive effect on students cognitive learning outcomes.Â Keywords: Assessment Instruments, Critical Thinking Skills, Acid-Base Materials